ASME 2009 InterPACK Conference, Volume 1 2009
DOI: 10.1115/interpack2009-89070
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Penetration of Phase Change Material in Carbon Foam for Transient Thermal Management

Abstract: Phase Change Materials (PCMs) are used for thermal management and are ideal for cyclic operations due to their high capacity to store heat. Most PCMs do not exhibit sufficient conductivity to be effective at larger sizes. Enhancing conductivity can be done in a number of ways including carbon foam. It is not widely known how well PCMs penetrate inside the carbon foam structure. Initial research suggests that the carbon foam-PCM matrix acts more as a conductor than a thermal storage device. Through the use micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Sanusi and Fleischer [19] found that it is difficult to fully penetrate PCM into all pores of graphite foam. This finding supports the theory of Py et al [20] in which PCM impregnation percentage is a function of average pore radius, surface tension of the PCM in its liquid phase and viscosity of the PCM in its liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Sanusi and Fleischer [19] found that it is difficult to fully penetrate PCM into all pores of graphite foam. This finding supports the theory of Py et al [20] in which PCM impregnation percentage is a function of average pore radius, surface tension of the PCM in its liquid phase and viscosity of the PCM in its liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…For that purpose, carbon foams with different porosities and different thermal conductivities were tested as porous matrices while paraffin wax was used as the PCM filling the pores. Sanusi et al [27] investigated the penetration of phase-change materials in carbon foam for transient thermal management. Wu and Xing [28] developed a mathematical model based on the energy conservation equation to predict the thermal behaviour and the performances of a latent-heat storage unit, using graphite foam filled with PCM in an electronic cooling system for power applications.…”
Section: Introductionmentioning
confidence: 99%